Characterization and mapping of RNase III cleavage sites in VSV genome RNA. - Wertz, G W (1981)
Ribonuclease III cleaves the genome RNA of vesicular stomatitis virus (VSV) to yield an array of fragments which range in size from 3.5 to 0.1 x 10(6) daltons under partial digestion conditions. The locations of the RNase III cleavage sites which give rise to these fragments have been ordered relative to the 3' end of the virion RNA by digestion of 3' end-labeled RNA. Based on a map of the cleavage sites we predicted that fragments having the same size could be generated which contain information from each gene. Annealing of individual VSV mRNA probes to Northern blots of the separated RNase III-generated fragments confirmed that fragments having the same size are, in fact, generated which contain information from each coding region of the VSV genome. Analysis of maps of partial digestion products indicates that fragments having the same size arise repeatedly along the 3' half of the genome. The cleavage of VSV RNA by RNase III can be detected only if the nuclease treated molecules are denatured. This suggest that the structure features in VSV RNA which signal cleavage involve areas of higher order RNA structure.